In vitro SOD-like activity of mono- and di-copper complexes with a phosphonate substituted SALAN-type ligand. (1st June 2019) - Székács, Inna; Tokarz, Paweł; Horvath, Robert; Kovács, Krisztina; Kubas, Adam; Shimura, Mari; Brasun, Justyna; Murzin, Vadim; Caliebe, Wolfgang; Szewczuk, Zbigniew; Paluch, Aneta; Wojnárovits, László; et al.
Abstract: SALEN- and SALAN-based complexes with catalytically active metal centers are very promising small molecules to be utilized as part of antioxidant therapies. Here we discuss a modified SALAN-type molecule armed with two phosphonate groups that significantly increase its water solubility and aid to furnish mono- or dinuclear complexes with Cu 2+ ions. The regulation of the SOD-mimicking ( i.e., catalytic) disproportionation reaction of the superoxide radical anion (O2 − ) at pH ~7.5 could be achieved by adjusting the metal-to-ligand stoichiometry as confirmed by McCord-Fridovich and pulse radiolysis tests. The higher antioxidant activity of the dicopper complex can be explained by the better access of O2 − to the copper centers and their more positive Cu(II)/Cu(I) redox potential. Simultaneously the analysis of in vitro effect on cells morphology indicates that cytotoxicity is also affected by the metal-to-ligand ratio, however, the active complex molecules do not show notable cytotoxicity that, together with the observed SOD-like activities, makes them potential candidates for antioxidant therapies. Graphical abstract: Image 1 Highlights: Phosphonate groups affect coordination of Cu(II) to a SALAN ligand and increase water solubility. SOD-like activity and overall cell toxicity are both affected by Cu/ligand ratio. The SOD-mimc 1Cu/ligand complex is well tolerated by living cells.